Non-cultural diagnostic methods of fungal keratitis - K.I. Bel'skaja; Obrubov A. S (РМЖ "Клиническая офтальмология")
Belskaia K. I.1,2, Obrubov A. S.2 1 Pirogov Russian National Research Medical University 2 City Clinical Hospital named after S. P. Botkin, Branch № 1, Ophthalmological hospital, Moscow Cultural diagnostic methods are the most accurate and time-proven, but also time-consuming. Non-cultural methods of diagnostics are more rapid and therefore can be used as express diagnostic tests for infectious diseases of cornea. In this review the possibilities of common diagnostic methods of fungal infection have been summarized such as direct microscopy using different types of dyes, optical coherent tomography, polymerase chain reaction and mass spectrometry. The review also considers the advantages and disadvantages of each of the methods, describes materials used in the investigation as well as the problems of visual identification. It evaluates the possibilities of their application in clinical experience and prospects of their further development. Together these studies provide that none of the above-mentioned methods of diagnostics is the etalon. For more accurate diagnostics an ophthalmologist should better use a combination of diagnostic methods. The diagnostics of eye fungal infection needs further development. Key words: fungal keratitis, corneal infections, direct microscopy, confocal microscopy, optical coherence tomography, polymerase chain reaction, mass spectrometry. For citation: Belskaia K.I., Obrubov A.S.  Non-cultural diagnostic methods of fungal keratitis // RMJ “Clinical  ophthalmology”. 2018;1:37–41.